Analysis of Financial Reports In An Effort To Assess The Feasibility of Financial Performance At PT. Ruvi Rizqy Berkah - Runiar Satriya; Dwi Widi Hariyanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2023)
The development of the business means more competitive that each company to company resources management can be more professional. The purpose of this research among others is to know the existence of PT. Ruvi Rizqy Berkah with the performance of financial met requirements attempt on during the progress. About the development of PT. Ruvi Rizqy Berkah with the performance of the coming financial. To know of the existence of PT. Ruvi Rizqy Berkah capacity independently expansion or using foreign capital. The kind of research used is descriptive qualitative. The population of the research is all the company financial reports. PT. Ruvi Rizqy Berkah Samples from this research are company financial reports PT. Ruvi Rizqy Berkah for the 2017-2019 period. The data analysis by measuring the data and evaluate where corporate financial performance using the ratio of liquidity, the solvency, the ratio of profitability and activities. Based on the results of the analysis that has been done and can be summed up as follows PT. Ruvi Rizqy Berkah has good financial performance and requirements attempt on during the progress. The PT. Ruvi Rizqy Berkah capital as evidenced by enough outlets or branches takes investors to expand, this was apparent from two assets high value the company's activities